Effects of Different Control Practices on Soil and Water Erosion in Sloping Mango Orchard - Hu Bin; Zhang Hanyue; Li Xiaoming; Pan Hongbing; Bao Weikai (Shuitu baochi tongbao)
[Objective] The suitable measures for controlling serious soil erosion in sloping mango (Mangifera indica) orchards in Panzhihua City, Sichuan Province were determined. [Methods] The effects of two engineering practices (D1 and D2 treatment) and one biological practice (A) were measured on surface runoff, sediment, nutrient content in runoff, and soil properties. [Results] Total runoff volume for the Medicago sativa planting treatment (A) in the two-year trial period was 22 515 ml. Total runoff volume in the A and D2 treatments decreased by 45% and 16%, respectively, compared with the check treatment (CK). In addition, eight of the 17 runoff volumes measured in the A treatment were significantly lower than in CK. The total sediment of the A treatment in the two-year trial period was 1.65 kg, 28.3% lower than that of CK. There were no significant differences in nutrient contents in runoff or in soil properties due to the treatments. [Conclusion] In this arid valley area, the biological treatment of planting M. sativa between rows in sloping mango orchards can reduce surface runoff and sediment yield more effectively than the two engineering measures tested in this study, and achieve better soil erosion control.